2019
DOI: 10.1016/j.scitotenv.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of small-sized and irregularly shaped polyethylene microplastics affect Chironomus riparius life-history traits

Abstract: et al., Ingestion of small-sized and irregularly shaped polyethylene microplastics affect Chironomus riparius life-history traits, Science of the Total Environment,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 41 publications
2
74
3
Order By: Relevance
“…Deposit feeders may therefore be suitable as MP bioindicators in lotic freshwater systems since they are not only site-specific, but they can also indicate impacts over a period of time. In previous lab experiments, it has been shown that MP ingestion can affect the life history (Silva et al 2019 ) and survival, growth and emergence (Ziajahromi et al 2018 ) in chironomid larvae. Hence, those insects may also be negatively impacted by MP in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Deposit feeders may therefore be suitable as MP bioindicators in lotic freshwater systems since they are not only site-specific, but they can also indicate impacts over a period of time. In previous lab experiments, it has been shown that MP ingestion can affect the life history (Silva et al 2019 ) and survival, growth and emergence (Ziajahromi et al 2018 ) in chironomid larvae. Hence, those insects may also be negatively impacted by MP in the field.…”
Section: Discussionmentioning
confidence: 99%
“… 21 25 The ingestion and/or adsorption of MPs has been suggested to cause adverse effects on toxicological end points at various levels of biological organization, generally observed in laboratory test systems at relatively high exposure concentrations. 21 , 22 , 24 26 Furthermore, experimental work has suggested that effects of MPs can occur at the community level (e.g., biodiversity, species composition), 27 , 28 population level (e.g., abundance), 29 individual level (e.g., survival, reproduction, growth, feeding, emergence, embryonic development, mobility, and physiology), 21 , 22 , 25 , 30 or suborganismal level (e.g., inflammation, reduced lysosomal stability in the digestive gland, reduced antioxidant capacity, DNA damage, neurotoxicity, oxidative damage, gut dysbiosis and alteration of the genetic expression, the ionic exchange, and enzymatic activity). 1 , 10 , 26 , 31 35 Several studies have speculated that elevated MP concentrations can cause physical damage (i.e., blockage of food passage), leading to a feeling of satiation and a reduced feeding.…”
Section: Introductionmentioning
confidence: 99%
“…When discarded into the environment, microplastics can cause detrimental effects to insects, such as malformation and inhibition of metabolism and reproductive function (Lee et al 2013;Von Moos et al 2012;Wright et al 2013). More specifically, studies have demonstrated that polyethylene (PE) microplastics adversely affect survival, growth, and adult emergence in dipteran flies of the genus Chironomus (Ziajahromi et al 2018;Silva et al 2019). Conversely, it was also reported that microplastics had no significant effects on mortality and growth in the Culex mosquito (Al-Jaibachi et al 2019).…”
Section: Introductionmentioning
confidence: 99%